Análisis, diseño y codificación de un sistema informático para gestionar los talleres de capacitación otorgados por la Administración de la Federación de Barrios del Noroccidente de Quito - Díaz Subia, Renato Santiago (2016)
This technical project is developed to serve in the process: registration of students, enrollment in workshops and assignment of teachers, among others. This causes delays in implementation for the delivery of diplomas, certifications, legalization procedures and affecting decision-making, resulting in loss of information and time to users who need accurate, available, timely and reliable information. The software is scoped to investigate, analyze and propose the best solution to create a welfare system, so that all expectations Federation suburbs northwest of Quito longs are met. The software is developed in web environment.